MO794: Central Venous Catheter-Related Complications in Older Haemodialysis Patients: A Multicentre Observational Cohort Study. (3rd May 2022) - Van Oevelen, Mathijs; Heggen, Boudewijn; Abrahams, Alferso C; Rotmans, Joris; Snoeijs, Maarten; Vernooij, Robin; van Buren, Marjolijn; Meijvis, Sabine
Abstract: BACKGROUND AND AIMS: Central venous catheters (CVC) remain a commonly used vascular access option in haemodialysis, despite guidelines advising to preferably use arteriovenous fistulae. Compared to younger patients, the risk-benefit ratio of CVC in older patients might be more beneficial, but previous studies mainly focussed on catheter-related bacteraemia and/or assessed tunnelled CVC (TCVC) only. This study's aim was to compare all catheter-related infections and malfunctions in older patients with younger patients using all CVC subtypes. METHOD: We used data from DUCATHO, a multicentre observational cohort study in the Netherlands. All adult patients in whom a CVC was placed for haemodialysis between 2012–2016 were included. The primary endpoint was the occurrence of catheter-related infections, comparing patients aged ≥ 70 years with patients aged <70 years (reference). As secondary endpoints, catheter malfunctions and catheter removal due to either infection or malfunction were assessed. Using Cox proportional hazards and recurrent events modelling, hazard ratios (HR) with 95% confidence intervals (CI) were calculated with adjustment of prespecified confounders. Additionally, endpoints were assessed for non-tunnelled CVC (NTCVC) and TCVC separately. RESULTS: A total of 1595 patients with 2731 CVC (66.5% NTCVC, 33.1% TCVC) were included. Of these patients, 1001 (62.8%) were aged <70 years and 594 (37.2%) ≥70 years. No statistically significant difference was found for the occurrence of catheter-related infections (adjusted HR 0.80, 95% CI 0.62–1.02), catheter malfunction (adjusted HR 0.94, 95% CI 0.75–1.17) and catheter removal due to infection or malfunction (adjusted HR 0.94, 95% CI 0.80–1.11). Results were comparable when assessing NTCVC and TCVC separately. CONCLUSION: Patients aged ≥ 70 years and <70 years have a comparable risk for the occurrence of catheter-related infections and catheter malfunction. These findings may help when discussing treatment options with older patients starting haemodialysis and may inform the current debate on the best vascular access for these patients.